A case report of allergic eczematoid dermatitis around hemodialysis access due to iodine-containing disinfectant - Lu, Xiaomei; He, Jing; Ren, Liansheng; Yang, Rong; Liu, Shuhuan; Bai, Jingying; Tang, Yueqiu; Zeng, Yi; Wang, Yunmin; Zhang, Wei; Zhu, Dan (Frontiers in Immunology, 2025)
We report here a case of allergic eczematoid dermatitis related to hemodialysis access. The patient was initially suspected to have puncture needle allergies or dialyzer reactions until the patient develops a similar response after switching from an arteriovenous fistula (AVF) to a tunneled cuffed catheter (TCC) for dialysis. Thereby, we highly suspected that the allergen was the iodine-containing disinfectant used prior to dialysis, and the patient was ultimately diagnosed with iodine-containing disinfectant allergy. The patient’s dermatitis improved remarkably after switching to alcohol disinfection as well as taking oral steroids. Early identification and diagnosis of allergic reactions at the vascular access site can avoid contacting with allergens, accordingly prevent complications like infection and loss of precious vascular accesses in these patients.